A Dual Decomposition Approach to Partial Crosstalk Cancelation in a Multiuser DMT-xDSL Environment. (24th June 2007) - Vangorp Vangorp, Jan Jan; Tsiaflakis Tsiaflakis, Paschalis Paschalis; Moonen Moonen, Marc Marc; Verlinden Verlinden, Jan Jan; Ysebaert Ysebaert, Geert Geert
Abstract : In modern DSL systems, far-end crosstalk is a major source of performance degradation. Crosstalk cancelation schemes have been proposed to mitigate the effect of crosstalk. However, the complexity of crosstalk cancelation grows with the square of the number of lines in the binder. Fortunately, most of the crosstalk originates from a limited number of lines and, for DMT-based xDSL systems, on a limited number of tones. As a result, a fraction of the complexity of full crosstalk cancelation suffices to cancel most of the crosstalk. The challenge is then to determine which crosstalk to cancel on which tones, given a complexity constraint. This paper presents an algorithm based on a dual decomposition to optimally solve this problem. The proposed algorithm naturally incorporates rate constraints and the complexity of the algorithm compares favorably to a known resource allocation algorithm, where a multiuser extension is made to incorporate the rate constraints.